Determination of Total Alkaloid Content of Raru (Cotylelobium lanceolatum Craib) Bark Extract Using UV-ViS Spectrophotometry Method - andriani, cici; Daulay, Anny Sartika; Ridwanto, Ridwanto; Nasution, Haris Munandar (Indonesian Journal of Science and Pharmacy, 2023)
The raru plant (Cotylelobium  lanceolatum Craib) comes from the Dipterocarpaceae family. Raru bark is usually added to the wine to enhance the taste of the wine. raru bark has antidiabetic compounds as a lowering of sugar levels in the blood. The purpose of this study was to determine the alkaloids in the Raru plant (Cotylelobium   lanceolatum  Craib) and to determine the total alkaloid content found in the Raru plant (Cotylelobium  lanceolatum  Craib). The extraction method used is the maceration extraction method using methanol solvent with various concentrations which is then evaporated with a rotary evaporator. Whereas the quantitative test was carried out by means of the viscous extract obtained by adding 2 mL of Phosphate buffer with a pH of 4.7, 2 mL of bromocresol green (BCG), and measured at a wavelength of 272.705 nm. The yield of the extract from a concentration of 95% was 23.0779%, a concentration of 70% was 21.2144%, a concentration of 50% was 20.3274%. The correlation equation obtained from the caffeine curve is y = 0.0508X + 0.008 and the value of r = 0.999, and the levels of alkaloids with different extract concentrations. Actual alkaloid content in raru bark methanol extract 95% was 14.9094 ± 0.3697 mg/g, actual alkaloid content in raru bark methanol extract 70% was 10.0472 ± 0.4594 mg/g, actual alkaloid content in extract 50% raru bark methanol was 6.6260 ± 0.803.